Zinc in Wheat Grain, Processing, and Food - Wang, Min; Kong, Fanmei; Liu, Rui; Fan, Qingqi; Zhang, Xiaocun (Frontiers in Nutrition, 2020)
Improving zinc (Zn) content in wheat and its processed foods is an effective way to solve human Zn deficiency, which can cause a variety of diseases. This article summarizes the works on Zn in wheat grain, wheat processing, and wheat-derived foods. Grain Zn content in wheat was 31.84 mg·kg−1 globally but varied across continents, for example, 25.10 mg·kg−1 in Europe, 29.00 mg·kg−1 in Africa, 33.63 mg·kg−1 in Asia, and 33.91 mg·kg−1 in North America. Grain Zn content in wheat improved from 28.96 mg·kg−1 to 36.61 mg·kg−1 and that in flour increased from 10.51 mg·kg−1 to 14.82 mg·kg−1 after Zn fortification. Furthermore, Zn content varied in the different processed components of wheat, that is, Zn content was 12,58 mg·kg−1 in flour, 70.49 mg·kg−1 in shorts, and 86.45 mg·kg−1 in bran. Zn content was also different in wheat-derived foods, such as 13.65 mg·kg−1 in baked food, 10.65 mg·kg−1 in fried food, and 8.03 mg·kg−1 in cooked food. Therefore, the suitable Zn fortification, appropriate processing, and food type of wheat are important to meet people’s Zn requirement through wheat.